Self–Leadership in the Context of Engaging in Professional Behaviour Change and Modification (A Systematic Review Analysis) - Anika, Alice A.; Level, Rene T. (European Journal of Applied Sciences, 2024)
Despite the growing body of literature on self-leadership and behaviour change, there remains a need for further consolidated review on the existing research findings to provide a comprehensive understanding of the relationship between self-leadership and professional behaviour modification. This systematic review analysis aimed to fill this gap by synthesizing empirical studies that explored how self-leadership influenced behaviour change in professional contexts, identifying key themes, methodologies, and outcomes. The search was limited to peer-reviewed articles published in English from January 2000 to October 2023. The objective of the article reviewed identified effective self-leadership strategies that facilitate behaviour change in professional settings, the role of self-leadership in overcoming barriers to change, Enhancement of motivation, and sustained behavioural modifications and actionable insights for professionals frameworks that support self-leadership and effective behaviour change initiatives. Study Design applied the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines to ensure a comprehensive and transparent approach (Moher et al., 2009). Search Strategy used a systematic review across multiple electronic databases, including PubMed, PsycINFO, Scopus, and Web of Science. Data Extraction - Data were extracted from the selected articles using a standardized form. Quality Assessment used Mixed Methods Appraisal Tool (MMAT) (Pluye et al., 2011). Each study was rated based on criteria relevant to its design, and studies were categorized as high, moderate, or low quality. Data Synthesis applied narrative synthesis approach, common themes, patterns, and gaps. The results were organized into key categories of the role of self-leadership in motivation, goal-setting, and self-regulation. All studies were assessed for informed consent and ethical treatment of participants. The analysis revealed that self-leadership serves as a foundational framework for individuals seeking to modify their professional behaviours. The review identified key themes; self-awareness, self-regulation and positive self-talk techniques as significant in behaviour change and modification.